Glycoprotein 130 Cytokine Signal as a Therapeutic Target Against Cardiovascular Diseases - Yasushi Fujio; Makiko Maeda; Tomomi Mohri; Masanori Obana; Tomohiko Iwakura; Akiko Hayama; Tomomi Yamashita; Hiroyuki Nakayama; Junichi Azuma (Elsevier, 2011)
Abstract.: Postnatal cardiomyocytes have only limited capacity of proliferation. Therefore, the myocardium is intrinsically equipped with cardioprotective machineries and protects itself from pathological stresses. One of the most important cardioprotective systems is the signal network of autocrine/paracrine factors, including neurohumoral factors, growth factors, and cytokines. In this review, we focus on the roles of interleukin-6 (IL-6) family cytokines, also known as glycoprotein 130 (gp130) cytokines, in cardioprotection. These cytokines make a complex with their specific cytokine receptor α-subunits. The cytokine-receptor α-subunit complex binds to gp130, a common receptor of the IL-6 family, followed by the activation of JAK/STAT, ERK, and PI3 kinase/Akt pathways. In cardiomyocytes, signals through gp130 promote cell survival and angiogenesis through the JAK/STAT pathway. Activation of gp130 in cardiac stem cells induces their endothelial transdifferentiation, leading to neovascularization. Recently, accumulating evidence has revealed that altered JAK/STAT activity is associated with heart failure, suggesting that the JAK/STAT pathway is a therapeutic target against cardiovascular diseases. Interestingly, activation of the JAK/STAT pathway with interleukin-11 (IL-11) exhibits preconditioning effects in ischemia/reperfusion model. Moreover, IL-11 treatment after coronary ligation prevents cardiac remodeling through the JAK/STAT pathway. Since IL-11 is used for patients with thrombocytopenia, we propose that IL-11 is a candidate cytokine clinically available for cardioprotection therapy. Keywords:: interleukin-6 (IL-6), JAK/STAT, STAT3, glycoprotein 130 (gp130), interleukin-11 (IL-11)